Engineering application of power generation technology for adding and reducing silt in multi-sediment reservoir. Issue 1 (May 2021) - Zhou, Heng; Li, Yongqing; Xing, Ruijiao; Di, Shengjie; Lu, Xi; Sun, Haitao
Abstract: The uncoordinated relationship between water and sand is a major technical problem that has not been completely eradicated or resolved in the construction of water conservancy and hydropower in the world. In response to the problem of sedimentation, scientific research, design and operation units have carried out research and application of key technologies for the addition of sediment-laden reservoirs to reduce siltation and power generation. The research results have been successfully applied to the Liujiaxia Tao River Mouth Desilting Tunnel and Machine Expansion Project. The Liujiaxia Reservoir has successfully solved the sediment discharge and silt reduction, increased the effective storage capacity of the reservoir, improved the power generation efficiency of the reservoir, improved the water quality of the reservoir, and provided support for the long-term spatial deployment of water resources.